Эпоха завоеваний: роман / Сергей Карелин - Карелин Сергей (Фантастический боевик, 2002)
Экземпляры: ф.14 (20211119) / Инвентарный номер: 62357 / Цена: 10.00 / Авт.знак: К 22 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6